The SIR Model for COVID-19 in Malaysia - Suzelawati Zenian (2022)
In March 2020, the World Health Organization (WHO) declared COVID-19 as a global pandemic caused by severe acute respiratory syndrome. This virus is referred to as SARSCoV- 2 and the associated disease is COVID-19. It is an infectious disease that can easily be transmitted via respiratory droplets through direct or indirect contact. This paper presents an epidemiological model of COVID-19 in Malaysia by using Susceptible-Infected-Removed (SIR) as a forecasting model. Forecasting is a technique used to predict or estimate the trend or rate of change for future events. This method can provide a good forecasting result for evaluating public health and social measures in response to the COVID-19 epidemic and also to make timely plans.